1989
DOI: 10.1177/104990918900600504
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes and experiences of families with death determination in the home

Abstract: The purpose of this study is to describe the attitudes and experiences of family members with respect to death determination practices for the terminally ill clients of home care agencies. A sample of family 53 members in Southeast Michigan returned survey questionnaires. The findings indicate that police and emergency medical technicians most frequently respond to the call when a person with a terminal illness has died. Fifty percent of the family members reported feeling sad, 35 percent reported feeling reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Previous reports in the literature suggest the ability of family to be present during final resuscitation attempts/efforts has facilitated their adjustment to death and the grief process. [13][14][15] It also improved their impression of the care provided. EMS staff informed family members of the death, satisfactorily provided answers in response to questions regarding treatment protocols, and provided care not only to the patient but also surviving family members, including grief support.…”
Section: Discussionmentioning
confidence: 86%
“…Previous reports in the literature suggest the ability of family to be present during final resuscitation attempts/efforts has facilitated their adjustment to death and the grief process. [13][14][15] It also improved their impression of the care provided. EMS staff informed family members of the death, satisfactorily provided answers in response to questions regarding treatment protocols, and provided care not only to the patient but also surviving family members, including grief support.…”
Section: Discussionmentioning
confidence: 86%
“…One study showed the ineffectiveness of EMTs in these roles (Critz, 1989). It is not surprising that many EMTs seek education on delivering effective death notifications and mitigating the family's grief (Coleman, 1993;Norton et al, 1992).…”
mentioning
confidence: 98%
“…There are important reasons to make plans for death that avoid using emergency medical services. Many families are often shocked and angry at the arrival of emergency personnel, because this may be considered an invasion of privacy and potential insinuation of foul play . One study found that police responded to 74% of home deaths of terminally ill individuals, emergency medical technicians 32%, and fire personnel 15% (total is >100% because of attendance by more than one type of emergency personnel) .…”
Section: Expected Deaths At Homementioning
confidence: 99%
“…Many families are often shocked and angry at the arrival of emergency personnel, because this may be considered an invasion of privacy and potential insinuation of foul play. 7,10 One study found that police responded to 74% of home deaths of terminally ill individuals, emergency medical technicians 32%, and fire personnel 15% (total is >100% because of attendance by more than one type of emergency personnel). 7 Because emergency personnel may have negative psychological effects on the family, it is prudent to advise families of terminally ill individuals that they can contact the funeral home directly in the event of an expected home death.…”
Section: Expected Deaths At Homementioning
confidence: 99%